2017
DOI: 10.1007/s12079-017-0400-z
|View full text |Cite
|
Sign up to set email alerts
|

The power of print reading: comics in the classroom

Abstract: Evidence from neuroscience and psychological studies supporting benefits of print reading over digital reading has recently been discussed in these columns (Perbal 2017 J. Cell Commun. Signal. 11:1-4). In the present commentary, I would like to add my perspective as a Humanities educator, and build upon the idea that print reading results in better comprehension, learning and communication. The argumentation that is presented herein is based on a study performed in a French Comics language class aimed at broad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The benefits of PHYCOM's teaching materials are: 1) it leads to understanding the concept, 2) it provides entertainment and increases knowledge, and 3) it creates a sense of pleasure when reading. This is supported by the results of research conducted by Gabaron (2017) that teaching materials in the form of comics can develop abilities related to comic literacy, increase interest in reading, and build emotional bonds between students and the object itself. Another study conducted by Lesmono et al (2012) also found that comics can increase students' learning motivation classically with a percentage of 89.93%.…”
Section: Correlation Between Aspects Of Phycom Validation Resultsmentioning
confidence: 75%
“…The benefits of PHYCOM's teaching materials are: 1) it leads to understanding the concept, 2) it provides entertainment and increases knowledge, and 3) it creates a sense of pleasure when reading. This is supported by the results of research conducted by Gabaron (2017) that teaching materials in the form of comics can develop abilities related to comic literacy, increase interest in reading, and build emotional bonds between students and the object itself. Another study conducted by Lesmono et al (2012) also found that comics can increase students' learning motivation classically with a percentage of 89.93%.…”
Section: Correlation Between Aspects Of Phycom Validation Resultsmentioning
confidence: 75%
“…The size was adjusted to the common comic size since the result of the questionnaire and interview showed that most of the students wanted to have a comic that resembled an actual comic. Deciding the size of a book is vital since the size of a book may influence the young learners' intention to read (Gabaron, 2017;Mohr, 2006). Therefore, the researchers decided the size of the book based on the students' requests.…”
Section: Layoutmentioning
confidence: 99%
“…Despite some initial resistance [8,9], the potential of comics as an educational tool has rapidly been recognized in the fields of education and psychology [10,11]. In recent decades, comics have indeed been used for public education purposes, and their use has been seen as a medium of choice as not only are they popular, but they can, when properly adapted, also act as a link to help children understand complex, nonfictional, and difficult concept or theme [10][11][12][13][14][15]. More recently, several empirical studies in the field of graphic medicine [16][17][18], on the use of comics, have shown that comics contribute to an overall improvement in community engagement on healthcare and medical issues [11,[19][20][21].…”
Section: Open Accessmentioning
confidence: 99%